Dampak Infrastruktur Teknologi, Kepemimpinan Organisasi dan Manajemen Waktu Terhadap Kinerja Pegawai di Dinas Komunikasi dan Informatika Kabupaten Dharmasraya dengan Kepuasan Kerja Sebagai Variabel Intervening - Rezki, Rahmat Zainul; Yulasmi, Yulasmi; Veri, Jhon (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to determine the impact of technological infrastructure, organizational leadership, and time management on employee performance at the Department of Communication and Information in Dharmasraya Regency with job satisfaction as an intervening variable. The method used is quantitative with path analysis techniques, distributing a questionnaire to 50 respondents. The research results show a positive and significant influence of technological infrastructure on job satisfaction. There is a positive and significant influence of leadership on job satisfaction. There is a positive and insignificant influence of time management on job satisfaction. There is a positive and significant influence of technological infrastructure on employee performance. There is a positive and insignificant influence of leadership on employee performance. There is a positive and significant influence of time management on employee performance. There is a positive and insignificant influence of job satisfaction on employee performance. Job satisfaction is able to mediate the influence of technological infrastructure on employee performance. Job satisfaction is able to mediate the influence of leadership on employee performance. Job satisfaction is able to mediate the influence of time management on employee performance.